2021
DOI: 10.1242/dmm.047449
|View full text |Cite
|
Sign up to set email alerts
|

Modelling epilepsy in the mouse: challenges and solutions

Abstract: In most mouse models of disease, the outward manifestation of a disorder can be measured easily, can be assessed with a trivial test such as hind limb clasping, or can even be observed simply by comparing the gross morphological characteristics of mutant and wild-type littermates. But what if we are trying to model a disorder with a phenotype that appears only sporadically and briefly, like epileptic seizures? The purpose of this Review is to highlight the challenges of modelling epilepsy, in which the most ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 227 publications
(143 reference statements)
0
33
1
1
Order By: Relevance
“…Colorless asterisks indicate wild-type and black asterisks indicate GluA1C811S mice. (Guillemain et al, 2012;Löscher, 2016;Löscher, 2017;Marshall et al, 2021). More than a hundred genes have been identified as causative genes for epilepsy to date and a lot of epilepsy-related mutations locate on loci coding ion channels (Helbig and Ellis, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorless asterisks indicate wild-type and black asterisks indicate GluA1C811S mice. (Guillemain et al, 2012;Löscher, 2016;Löscher, 2017;Marshall et al, 2021). More than a hundred genes have been identified as causative genes for epilepsy to date and a lot of epilepsy-related mutations locate on loci coding ion channels (Helbig and Ellis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Symptom-mimicking behavioral outcomes in these models provide an indicator of pharmacological effects on epileptic seizure. In addition to acute seizure models using drugs and chemically or electrically kindled rodents, genetically modified mice have been used to discover novel and highly effective anticonvulsants (Marshall et al, 2021). In these researches, many AEDs have been developed so far, which target ion channels, such as voltagegated sodium channel (VGSC) α-subunits Na V 1.1 and Na V 1.2 and β-subunit (Kaplan et al, 2016), T-type voltage-gated calcium channel (VGCC) α1H-subunit Ca V 3.2 (Zamponi et al, 2009), M-type potassium channel subunits (Springer et al, 2021), GABA A receptor α1and γ2-subunits (Treiman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are many different types of seizures; generalized seizures, that involve large bilateral brain areas, comprehend one of the three main categories of epilepsy ( Marshall et al, 2021 ). Generalized seizures can be presented as tonic-clonic seizures or as absence epilepsy.…”
Section: Inosine and Epilepsymentioning
confidence: 99%
“…Tonic-clonic seizures are the most common seizures associated with epilepsy. During the tonic phase, there is loss of consciousness and the body is entirely rigid, and in the clonic phase, there is uncontrolled jerking of the limbs and possible difficulty breathing ( Marshall et al, 2021 ). Absence epilepsy is a brief non-convulsive seizure associated with sudden abruptness in consciousness ( Jafarian et al, 2020 ).…”
Section: Inosine and Epilepsymentioning
confidence: 99%
“…Biosamples can also be influenced by anti-seizure treatments, which alter the expression profile and analytes obtained from a liquid biopsy [25,39,40]. Outside of sample type and time of collection, there are also limitations in accurately modeling epilepsy to mirror similar onset, progression, frequency, and phenotype to that of human epilepsies [41] . Research models of pilocarpine-induced epilepsy in-vivo have shown that development and progression can occur much faster in animals compared to human models [23,42].…”
Section: Challengesmentioning
confidence: 99%